Requirements For Implementing E-Management In The Lattakia Directorate Of Education - جرعا, شادي; غدير , باسم; زين العابدين, دانيا (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of the research is to study the availability of the requirements of the electronic administration application in the Directorate of Education in Latakia, the Department of Vocational Education. The researcher has taken into consideration the four requirements that have been agreed upon by most studies, which are administrative, financial, technical, and human requirements. A questionnaire was distributed to 98 administrators in the directorate, school principals, heads of technical classes and heads of departments, and a set of results was reached, the most important of which is that there are administrative and financial requirements but need to be strengthened, while technical and human requirements are not available, and the researcher has recommended a number of recommendations, including directing Financial support and work immediately to provide all the requirements for the electronic administration with the use of expertise in this field, and the school administrators enrolled in intensive courses on the application of electronic management and the process of electronic linking with schools and the ministry, and activation Incentives appropriate for all administrative staff and shareholders by providing requirements and so for the rapid transition to the application of E-administration.